Diffusion preparation method of Fe-rich high-coercivity samarium-cobalt magnet

By using PrCu and SnFe diffusion treatment in 2:17 SmCo permanent magnets, the polarization of mesh Cu elements and Fe element distribution are formed, and the microstructure problem of magnets caused by Fe content is solved, and the magnetic performance and coercion of magnets are improved. The power of the system achieves efficient improvement of magnetic performance and optimization of production efficiency.

CN119296941AActive Publication Date: 2025-01-10TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411546882.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-10
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the magnetic performance of the 2:17 SmCo permanent magnet, especially when the Fe-rich content is too high, the microstructure of the magnet deteriorates, resulting in a decrease in magnetic performance, and the diffusion of the low melting point phase cannot effectively improve the residual magnetism of the magnet and Maximum magnetic energy product.

Method used

A method of diffusion preparation of samarium-cobalt magnets with high coercivity is adopted, including adding PrCu and SnFe suspension solutions to the samarium-cobalt permanent magnet alloy raw material for diffusion treatment, through the dividing of the mesh Cu element and the diffusion of Fe elements. Form a good cellular tissue structure to improve the saturation magnetization and residual magnetism of the magnet.

Benefits of technology

Through this method, the coercive force and magnetic properties of samarium-cobalt magnets are significantly improved, the aging treatment time is shortened, the production efficiency is improved, and the prepared magnets are excellent in performance, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296941A_ABST
    Figure CN119296941A_ABST
Patent Text Reader

Abstract

A diffusion preparation method of a Fe-rich high-coercivity samarium-cobalt magnet belongs to the technical field of magnetic material preparation, solves the technical problems that the Fe-rich samarium-cobalt magnet is not easy to form a good cellular structure and the process flow is long, and comprises the following steps: S1, weighing a samarium-cobalt permanent magnet alloy raw material, and preparing an alloy ingot; s2, alloy particles are prepared through a mechanical crushing method, and the alloy particles are prepared into alloy powder; s3, the samarium-cobalt alloy powder is subjected to magnetic field orientation forming and cold isostatic pressing forming, and a green body is prepared; s4, performing sintering solution treatment on the green body to prepare a sintered samarium-cobalt permanent magnet blank, and processing the blank into a samarium-cobalt magnet sheet; s5, performing primary PrCu diffusion treatment on the samarium-cobalt magnet sheet; s6, the magnet sheet is subjected to secondary SnFe diffusion treatment; and S7, performing aging treatment on the secondary diffusion sheet to obtain the samarium-cobalt permanent magnet. The preparation method provided by the invention is easy to operate, control and industrialize, and the prepared Fe-rich sintered samarium-cobalt magnet is excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic material preparation, and in particular relates to a diffusion preparation method for an Fe-rich high-coercivity samarium-cobalt magnet. Background Art

[0002] Since its advent, the second-generation rare earth permanent magnet material 2:17 SmCo permanent magnet has been favored for its excellent magnetic properties. It has developed rapidly in scientific research, production and application, and is widely used in national defense and military industry, aerospace, medical equipment, microwave devices, transportation, high-end motors and many other fields.

[0003] 2:17 SmCo permanent magnet has a typical cellular structure, in which the 2:17R cellular phase has a higher solubility for Fe element, which can provide high saturation magnetization for the magnet; 1:5H cell wall phase has a higher solubility for Cu element. Through appropriate heat treatment process, Cu element can be enriched at the cell wall and form a certain concentration gradient, so that the magnet obtains high coercivity; in addition to the cellular phase and cell wall phase, there is also a lamellar Zr-rich phase structure in the magnet. The lamellar phase also plays an important role in the magnet. Many people believe that it provides a channel for element diffusion during the aging process. It is precisely because of such a complex microstructure that the 2:17 sintered SmCo magnet exhibits excellent comprehensive magnetic properties. In order to prepare high-performance SmCo magnets, increasing the Fe content is one of the key processes, but too high Fe content will have a certain impact on the microstructure of the magnet, thereby deteriorating the magnetic properties of the magnet. Improving the microstructure of Fe-rich samarium cobalt magnets, optimizing the preparation process, and thus improving the magnetic properties of magnets are of great significance to the development of the samarium cobalt industry.

[0004] At present, in the patent document "2-17 type samarium cobalt permanent magnet material and its preparation method and application" (publication number: CN113593882 A), a metal Cu layer is applied to the surface of the samarium cobalt sintered body, and the Cu content in the magnet grain boundary is improved by diffusion treatment to improve the magnetic properties of the magnet, but the Cu element is a non-magnetic element, and the diffusion of Cu will cause the remanence of the magnet to decrease. In the patent document "A method for improving the magnetic properties of samarium cobalt permanent magnet material" (publication number: CN 112038083 A), a low-melting-point phase diffusion source is applied to the surface of the base material by coating and / or encapsulation for diffusion treatment to improve the magnetic properties of the magnet, but it cannot solve the problem of deterioration of the magnet microstructure caused by excessive Fe content, and the diffusion of the low-melting-point phase RE-TM cannot effectively improve the remanence and maximum magnetic energy product of the magnet. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art and solve the technical problems that Fe-rich SmCo magnets are not easy to form a good cellular structure and the preparation process is long, the present invention provides a diffusion preparation method for Fe-rich high coercive force SmCo magnets, thereby improving the microstructure of Fe-rich SmCo magnets, improving production efficiency, and effectively improving the magnetic properties of 2:17 type SmCo magnets.

[0006] In order to achieve the above objectives, the present invention is implemented through the following technical solutions.

[0007] A diffusion preparation method for an Fe-rich high coercivity samarium-cobalt magnet comprises the following steps: S1. First, weigh the samarium cobalt permanent magnet alloy raw material according to the following composition and its weight percentage: (Sm 1-x Re x ): 23%~25.5%, Fe: 16%~23%, Zr: 2.1%~3%, Cu: 4%~6%, and the balance is Co; wherein 0≤x≤0.3, Re is one or more of Pr, Nd, Gd, Dy, Tb, Er, Y or Ho; then, the weighed samarium cobalt permanent magnet alloy raw material is melted in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3-5 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at a temperature of 1200-1215°C for 1-2h; then, the sintered green body is cooled to 1160-1180°C with the furnace for solution treatment, and the heat preservation time is 4-10h. After the solution treatment, the green body is quickly cooled to room temperature to obtain a solid solution green body of samarium cobalt magnet; through the solution treatment, the samarium cobalt magnet can form a uniform 1:7H phase, which is prepared for subsequent diffusion and the formation of a good cellular structure; finally, the solid solution green body of samarium cobalt magnet is processed into a samarium cobalt magnet slice by a slicer; affected by the diffusion depth of the elements, when the thickness of the magnet is too large, the diffused elements cannot fully enter the interior of the magnet, resulting in a poor diffusion effect, therefore, the samarium cobalt magnet needs to be processed into a slice with a thickness of 3-7mm; S5. First, prepare a PrCu suspension solution; then, evenly coat the PrCu suspension solution on the surface of the SmCo magnet sheet (upper and lower surfaces) and blow dry; finally, perform a diffusion treatment on the coated SmCo magnet sheet in a tube furnace, the diffusion treatment temperature is 1140-1150°C, the diffusion treatment time is 4-8h, and the SmCo magnet diffusion sheet is obtained after cooling out of the furnace; after the magnet is solid-solution treated in step S4, a uniform 1:7H phase can be obtained, and then a diffusion of PrCu is performed at 1140-1150°C, which is slightly lower than the solid-solution temperature, to promote the network segregation of Cu elements. When preparing Fe-rich SmCo magnets, due to the high content of Fe elements, the cell size of the magnet becomes larger and it is not easy to form a complete cell structure, so that the magnetic domain cannot be effectively pinned, resulting in a decrease in the coercive force of the magnet. The present invention diffuses PrCu compounds to allow a certain amount of Cu elements to enter the interior of the magnet and be distributed in a network-like cluster. These clustered Cu elements will become nucleation sites for the Cu-rich cell wall phase in the subsequent aging process, which is beneficial to the formation of the cell wall. Therefore, it promotes the Fe-rich magnet to form a complete cellular structure, thereby obtaining a higher coercive force. However, the Cu element is a non-magnetic element, and its entry will cause the saturation magnetization of the magnet to decrease, while the entry of the Pr element will form Pr2Co 17 phase, whose saturation magnetization is greater than that of Sm2Co 17 , thus increasing the saturation magnetization of the magnet, compensating for the decrease in magnetic properties of the magnet caused by the entry of non-magnetic Cu elements; S6. First, prepare a SnFe suspension solution; then, evenly coat the SnFe suspension solution on the surface of the thin slice prepared in step S5 and blow dry; finally, subject the coated samarium cobalt magnet thin slice to a secondary diffusion treatment in a tubular furnace, the secondary diffusion treatment temperature is 850~900℃, the diffusion treatment time is 2~4h, and the thin slice is cooled and taken out of the furnace to obtain a samarium cobalt magnet secondary diffusion thin slice; the secondary diffusion treatment can allow the Fe element to enter the cell, increase the saturation magnetization of the magnet, and promote the rapid formation of a cellular structure. By diffusing SnFe compounds, excess Fe elements can be diffused into the magnet, and Fe elements can replace Co elements without destroying the cellular structure of the magnet, thereby increasing the saturation magnetization of the magnet and improving the remanence and maximum magnetic energy product of the magnet. The addition of Sn elements is conducive to the full and rapid diffusion of Fe elements; S7. Perform aging treatment on the samarium cobalt magnet secondary diffusion sheet obtained after the treatment in step S6. The aging treatment process is as follows: heat the samarium cobalt magnet secondary diffusion sheet to 800-850°C, keep it warm for 1-4 hours, then cool it to 400°C at a rate of 1.5°C / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain Fe-rich high coercive force samarium cobalt magnet.

[0008] Furthermore, in step S4, the thickness of the samarium cobalt magnet sheet is 3-7 mm.

[0009] Furthermore, in step S5, the preparation method of the PrCu suspension solution is: first, 40% by mass of Pr and 60% by mass of Cu are smelted in an arc induction melting furnace to obtain a PrCu alloy ingot; then, the PrCu alloy ingot is crushed into a PrCu alloy powder with a particle size of 500-1000nm by high-energy ball milling, which is conducive to its uniform coating on the surface of the magnet sheet and improving the diffusion uniformity, so that the magnetic properties of the magnet after diffusion are more consistent; finally, the PrCu alloy powder is mixed and stirred evenly with anhydrous ethanol to obtain a PrCu suspension solution.

[0010] Furthermore, in the step S5, the prepared samarium cobalt magnet diffusion sheet has a network Cu element segregation structure.

[0011] Furthermore, in step S6, the SnFe suspension solution is prepared by: first, 5% by mass of Sn and 95% by mass of Fe are smelted in an arc induction melting furnace to obtain a SnFe alloy ingot; then, the SnFe alloy ingot is crushed into a SnFe alloy powder of 500-1000 nm by high-energy ball milling, which is conducive to uniform diffusion of elements; finally, the SnFe alloy powder is mixed and stirred evenly with anhydrous ethanol to obtain a SnFe suspension solution.

[0012] Furthermore, the PrCu alloy powder and the SnFe alloy powder are mixed with anhydrous ethanol at a mass ratio of 1:9.

[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention diffuses PrCu compounds in the solid solution samarium cobalt magnet flakes. After the Cu element diffuses into the magnet, it is distributed in a network-like manner, which can become the nucleation site of the Cu-rich cell wall phase in the subsequent aging process, which is conducive to the formation of a good cellular structure of the Fe-rich magnet, thereby obtaining a higher coercive force; at the same time, the Pr element enters the magnet, due to the Pr2Co 17 The saturation magnetization is greater than that of Sm2Co 17 , which can make up for the decrease in the saturation magnetization intensity of the magnet caused by the entry of non-magnetic Cu elements; 2. The present invention diffuses SnFe compounds to allow excess Fe elements to enter the magnet, and the diffusion temperature is 850-900°C, so that the saturation magnetization of the magnet can be increased without destroying the cellular structure of the magnet, thereby increasing the remanence and maximum magnetic energy product of the magnet. The addition of Sn elements is conducive to the full and rapid diffusion of Fe elements. 3. In the present invention, the Cu element is segregated by primary diffusion, which is beneficial to the rapid formation of a cellular structure during the aging process; in addition, in the secondary diffusion process, the diffusion temperature of 850-900°C promotes the formation of a cellular structure, thereby greatly shortening the subsequent aging treatment time and improving production efficiency.

[0014] In conclusion, the preparation method provided by the present invention is easy to operate, control and industrialize, and the prepared sintered samarium cobalt magnet has excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram of the process flow of the diffusion preparation method of the Fe-rich high coercivity samarium cobalt magnet of the present invention; Figure 2 This is a typical network-like Cu element segregation microstructure of the samarium cobalt sheet obtained after a single diffusion of PrCu in the present invention. DETAILED DESCRIPTION

[0016] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the examples are based on conventional experimental conditions. Example 1

[0017] A diffusion preparation method for an Fe-rich high coercivity samarium-cobalt magnet comprises the following steps: S1. First, weigh a raw material of a samarium-cobalt permanent magnet alloy according to the following composition and its weight percentage: Sm: 23%, Fe: 16%, Zr: 2.5%, Cu: 5%, Co: 53.5%; then, melt the weighed raw material of the samarium-cobalt permanent magnet alloy in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3.8 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1215°C for 2h; then, cooling the sintered green body to 1180°C with the furnace for solution treatment, and the heat preservation time is 4h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 5mm thick green body of samarium cobalt magnet slice by a slicer; S5. First, prepare a PrCu suspension solution. The preparation method of the PrCu suspension solution is as follows: first, 40% by mass of Pr and 60% by mass of Cu are melted in an arc induction melting furnace to obtain a PrCu alloy ingot; then, the PrCu alloy ingot is crushed into a PrCu alloy powder with a particle size of 500-1000nm by high-energy ball milling; finally, the PrCu alloy powder is mixed and stirred evenly with anhydrous ethanol, and the mass ratio of the PrCu alloy powder to the anhydrous ethanol is 1:9 to obtain a PrCu suspension solution; then, the PrCu suspension solution is evenly coated on the surface of the samarium cobalt magnet sheet and blown dry; finally, the coated samarium cobalt magnet sheet is subjected to a diffusion treatment in a tubular furnace, the diffusion treatment temperature is 1150°C, the diffusion treatment time is 4h, and the sheet is cooled and taken out of the furnace to obtain a samarium cobalt magnet diffusion sheet, and the obtained samarium cobalt magnet diffusion sheet has a network Cu element segregation structure; S6. First, prepare a SnFe suspension solution. The preparation method of the SnFe suspension solution is as follows: first, smelt 5% Sn by mass and 95% Fe by mass in an arc induction melting furnace to obtain a SnFe alloy ingot; then, use a high-energy ball mill to crush the SnFe alloy ingot into a SnFe alloy powder of 500-1000nm; finally, mix and stir the SnFe alloy powder with anhydrous ethanol, the mass ratio of the SnFe alloy powder to the anhydrous ethanol is 1:9, and obtain a SnFe suspension solution; then, evenly coat the SnFe suspension solution on the surface of the slice prepared in step S5 and blow dry; finally, perform a secondary diffusion treatment on the coated samarium cobalt magnet slice in a tubular furnace, the secondary diffusion treatment temperature is 900°C, the diffusion treatment time is 4h, and the slice is cooled and taken out of the furnace to obtain a samarium cobalt magnet secondary diffusion slice; S7. Perform aging treatment on the samarium cobalt magnet secondary diffusion sheet obtained after the treatment in step S6. The aging treatment process is as follows: heat the samarium cobalt magnet secondary diffusion sheet to 850°C, keep it warm for 4 hours, then cool it to 400°C at a rate of 1.5°C / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain Fe-rich high coercive force samarium cobalt magnet.

[0018] The magnetic properties of the Fe-rich high coercivity samarium cobalt magnet prepared in Example 1 are as follows: r =11.41kGs, magnetic energy product (BH) m =31MGOe, intrinsic coercivity H cj =33.38kOe.

[0019] Comparative Example 1

[0020] Comparative Example 1 does not use the S5 primary diffusion and S6 secondary diffusion processes in Example 1, and other preparation processes are the same as those in Example 1.

[0021] A method for preparing a sintered samarium cobalt permanent magnet comprises the following steps: S1. First, weigh a raw material of a samarium-cobalt permanent magnet alloy according to the following composition and its weight percentage: Sm: 23%, Fe: 16%, Zr: 2.5%, Cu: 5%, Co: 53.5%; then, melt the weighed raw material of the samarium-cobalt permanent magnet alloy in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3.8 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1215°C for 2h; then, cooling the sintered green body to 1180°C with the furnace for solution treatment, and the heat preservation time is 4h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 5mm thick green body of samarium cobalt magnet slice by a slicer; S5. Perform aging treatment on the samarium cobalt magnet slice obtained after the treatment in step S4. The aging treatment process is as follows: heat the samarium cobalt magnet slice to 850° C., keep it at this temperature for 4 hours, then cool it to 400° C. at a rate of 1.5° C. / min, keep it at this temperature for 1 hour, and then quickly air-cool it to room temperature to obtain a sintered samarium cobalt permanent magnet.

[0022] The magnetic properties of the sintered samarium cobalt permanent magnet prepared in Comparative Example 1 are: remanence B r =11.22kGs, magnetic energy product (BH) m =29.93MGOe, intrinsic coercivity H cj =33.42kOe. Example 2

[0023] A diffusion preparation method for an Fe-rich high coercivity samarium-cobalt magnet comprises the following steps: S1. First, weigh the samarium cobalt permanent magnet alloy raw material according to the following composition and its weight percentage: Sm: 24%, Fe: 23%, Zr: 2.8%, Cu: 5.5%, Co: 44.7%; then, melt the weighed samarium cobalt permanent magnet alloy raw material in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3.4 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1200°C for 1.5h; then, cooling the sintered green body to 1160°C with the furnace for solution treatment, and the heat preservation time is 10h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a samarium cobalt magnet sheet with a thickness of 7mm by a slicer; S5. First, prepare a PrCu suspension solution. The preparation method of the PrCu suspension solution is the same as that of Example 1. Then, the PrCu suspension solution is evenly coated on the surface of the samarium cobalt magnet sheet and blown dry. Finally, the coated samarium cobalt magnet sheet is subjected to a diffusion treatment in a tube furnace. The diffusion treatment temperature is 1140° C. and the diffusion treatment time is 8 hours. The sheet is cooled and taken out of the furnace to obtain a samarium cobalt magnet diffusion sheet. The obtained samarium cobalt magnet diffusion sheet has a network Cu element segregation structure. S6. First, prepare a SnFe suspension solution. The method for preparing the SnFe suspension solution is the same as that in Example 1. Then, evenly coat the SnFe suspension solution on the surface of the slice prepared in step S5 and blow dry. Finally, perform a secondary diffusion treatment on the coated samarium cobalt magnet slice in a tube furnace. The secondary diffusion treatment temperature is 850° C., the diffusion treatment time is 2 h, and the slice is cooled and taken out of the furnace to obtain a samarium cobalt magnet secondary diffusion slice. S7. Perform aging treatment on the samarium cobalt magnet secondary diffusion sheet obtained after the treatment in step S6. The aging treatment process is as follows: heat the samarium cobalt magnet secondary diffusion sheet to 800° C., keep it warm for 3 hours, then cool it to 400° C. at a rate of 1.5° C. / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain Fe-rich high coercive force samarium cobalt magnet.

[0024] The magnetic properties of the Fe-rich high coercivity samarium cobalt magnet prepared in Example 2 are as follows: r =11.84kGs, magnetic energy product (BH) m =33.18MGOe, intrinsic coercivity H cj =23.25kOe. Comparative Example 2

[0025] Comparative Example 2 does not use the S5 primary diffusion and S6 secondary diffusion processes in Example 2, and the other preparation processes are the same as those in Example 2.

[0026] A method for preparing a sintered samarium cobalt permanent magnet comprises the following steps: S1. First, weigh the samarium cobalt permanent magnet alloy raw material according to the following composition and its weight percentage: Sm: 24%, Fe: 23%, Zr: 2.8%, Cu: 5.5%, Co: 44.7%; then, melt the weighed samarium cobalt permanent magnet alloy raw material in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3.4 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1200°C for 1.5h; then, cooling the sintered green body to 1160°C with the furnace for solution treatment, and the heat preservation time is 10h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a samarium cobalt magnet sheet with a thickness of 7mm by a slicer; S5. Perform aging treatment on the samarium cobalt magnet slice obtained after the treatment in step S4. The aging treatment process is as follows: heat the samarium cobalt magnet slice to 800° C., keep it warm for 3 hours, then cool it to 400° C. at a rate of 1.5° C. / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain a sintered samarium cobalt permanent magnet.

[0027] The magnetic properties of the sintered samarium cobalt permanent magnet prepared in Comparative Example 2 are: remanence B r =11.65kGs, magnetic energy product (BH) m =32.23MGOe, intrinsic coercivity H cj =30.18kOe. Example 3

[0028] A diffusion preparation method for an Fe-rich high coercivity samarium-cobalt magnet comprises the following steps: S1. First, weigh a samarium cobalt permanent magnet alloy raw material according to the following composition and its weight percentage: Sm: 25.5%, Fe: 22%, Zr: 2.1%, Cu: 6%, Co: 44.4%; then, melt the weighed samarium cobalt permanent magnet alloy raw material in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 4.5 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1205°C for 1h; then, cooling the sintered green body to 1165°C with the furnace for solution treatment, and the heat preservation time is 10h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 6mm thick green body of samarium cobalt magnet slice by a slicer; S5. First, prepare a PrCu suspension solution. The preparation method of the PrCu suspension solution is the same as that of Example 1. Then, the PrCu suspension solution is evenly coated on the surface of the samarium cobalt magnet sheet and blown dry. Finally, the coated samarium cobalt magnet sheet is subjected to a diffusion treatment in a tube furnace. The diffusion treatment temperature is 1140° C. and the diffusion treatment time is 8 hours. The sheet is cooled and taken out of the furnace to obtain a samarium cobalt magnet diffusion sheet. The obtained samarium cobalt magnet diffusion sheet has a network Cu element segregation structure. S6. First, prepare a SnFe suspension solution. The method for preparing the SnFe suspension solution is the same as that in Example 1. Then, the SnFe suspension solution is evenly coated on the surface of the thin slice prepared in step S5 and blown dry. Finally, the coated samarium cobalt magnet thin slice is subjected to secondary diffusion treatment in a tube furnace. The secondary diffusion treatment temperature is 860° C., the diffusion treatment time is 2 h, and the thin slice is cooled and taken out of the furnace to obtain a samarium cobalt magnet secondary diffusion thin slice. S7. Perform aging treatment on the samarium cobalt magnet secondary diffusion sheet obtained after the treatment in step S6. The aging treatment process is as follows: heat the samarium cobalt magnet secondary diffusion sheet to 810°C, keep it warm for 3 hours, then cool it to 400°C at a rate of 1.5°C / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain Fe-rich high coercive force samarium cobalt magnet.

[0029] The magnetic properties of the Fe-rich high coercivity samarium cobalt magnet prepared in Example 3 are as follows: r =11.75kGs, magnetic energy product (BH) m =32.75MGOe, intrinsic coercivity H cj =29.96kOe. Comparative Example 3

[0030] Comparative Example 3 does not use the S5 primary diffusion and S6 secondary diffusion processes in Example 3, and the other preparation processes are the same as Example 3.

[0031] A method for preparing a sintered samarium cobalt permanent magnet comprises the following steps: S1. First, weigh a samarium cobalt permanent magnet alloy raw material according to the following composition and its weight percentage: Sm: 25.5%, Fe: 22%, Zr: 2.1%, Cu: 6%, Co: 44.4%; then, melt the weighed samarium cobalt permanent magnet alloy raw material in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 4.5 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1205°C for 1h; then, cooling the sintered green body to 1165°C with the furnace for solution treatment, and the heat preservation time is 10h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 6mm thick green body of samarium cobalt magnet slice by a slicer; S5. Perform aging treatment on the samarium cobalt magnet slice obtained after the treatment in step S4. The aging treatment process is as follows: heat the samarium cobalt magnet slice to 810° C., keep it warm for 3 hours, then cool it to 400° C. at a rate of 1.5° C. / min, keep it warm for 1 hour, and then quickly cool it to room temperature to obtain a sintered samarium cobalt permanent magnet.

[0032] The magnetic properties of the sintered samarium cobalt permanent magnet prepared in this comparative example 3 are: remanence B r =11.58kGs, magnetic energy product (BH) m =31.88MGOe, intrinsic coercivity H cj =31.26kOe. Example 4

[0033] A diffusion preparation method for an Fe-rich high coercivity samarium-cobalt magnet comprises the following steps: S1. First, weigh a raw material of a samarium-cobalt permanent magnet alloy according to the following composition and its weight percentage: Sm: 24.5%, Fe: 20%, Zr: 3%, Cu: 4%, Co: 48.5%; then, melt the weighed raw material of the samarium-cobalt permanent magnet alloy in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 4 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1210°C for 1.5h; then, cooling the sintered green body to 1170°C with the furnace for solution treatment, and the heat preservation time is 6h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 5mm thick green body of samarium cobalt magnet slice by a slicer; S5. First, prepare a PrCu suspension solution. The preparation method of the PrCu suspension solution is the same as that of Example 1. Then, the PrCu suspension solution is evenly coated on the surface of the samarium cobalt magnet sheet and blown dry. Finally, the coated samarium cobalt magnet sheet is subjected to a diffusion treatment in a tube furnace. The diffusion treatment temperature is 1145° C. and the diffusion treatment time is 6 hours. The sheet is cooled and taken out of the furnace to obtain a samarium cobalt magnet diffusion sheet. The obtained samarium cobalt magnet diffusion sheet has a network Cu element segregation structure. S6. First, prepare a SnFe suspension solution. The method for preparing the SnFe suspension solution is the same as that in Example 1. Then, the SnFe suspension solution is evenly coated on the surface of the slice prepared in step S5 and blown dry. Finally, the coated samarium cobalt magnet slice is subjected to secondary diffusion treatment in a tube furnace. The secondary diffusion treatment temperature is 870° C., the diffusion treatment time is 3 h, and the slice is cooled and taken out of the furnace to obtain a samarium cobalt magnet secondary diffusion slice. S7. Perform aging treatment on the samarium cobalt magnet secondary diffusion sheet obtained after the treatment in step S6. The aging treatment process is as follows: heat the samarium cobalt magnet secondary diffusion sheet to 830°C, keep it warm for 3 hours, then cool it to 400°C at a rate of 1.5°C / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain Fe-rich high coercive force samarium cobalt magnet.

[0034] The magnetic properties of the Fe-rich high coercivity samarium cobalt magnet prepared in Example 4 are as follows: r =11.68kGs, magnetic energy product (BH) m =32.41MGOe, intrinsic coercivity H cj =31.2kOe. Comparative Example 4

[0035] Comparative Example 4 does not use the S5 primary diffusion and S6 secondary diffusion processes in Example 4, and the other preparation processes are the same as those in Example 4.

[0036] A method for preparing a sintered samarium cobalt permanent magnet comprises the following steps: S1. First, weigh a raw material of a samarium-cobalt permanent magnet alloy according to the following composition and its weight percentage: Sm: 24.5%, Fe: 20%, Zr: 3%, Cu: 4%, Co: 48.5%; then, melt the weighed raw material of the samarium-cobalt permanent magnet alloy in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 4 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1210°C for 1.5h; then, cooling the sintered green body to 1170°C with the furnace for solution treatment, and the heat preservation time is 6h. After the solution treatment, the green body is rapidly cooled to room temperature to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 5mm thick green body of samarium cobalt magnet slice by a slicer; S5. Perform aging treatment on the samarium cobalt magnet slice obtained after the treatment in step S4. The aging treatment process is as follows: heat the samarium cobalt magnet slice to 830° C., keep it warm for 3 hours, then cool it to 400° C. at a rate of 1.5° C. / min, keep it warm for 1 hour, and then quickly cool it to room temperature to obtain a sintered samarium cobalt permanent magnet.

[0037] The magnetic properties of the sintered samarium cobalt permanent magnet prepared in this comparative example 4 are: remanence B r =11.52kGs, magnetic energy product (BH) m =31.59MGOe, intrinsic coercivity H cj =33.29kOe. Example 5

[0038] A diffusion preparation method for an Fe-rich high coercivity samarium-cobalt magnet comprises the following steps: S1. First, weigh a raw material of a samarium cobalt permanent magnet alloy according to the following composition and its weight percentage: Sm: 22.5%, Gd: 2%, Fe: 19%, Zr: 2.8%, Cu: 5.5%, Co: 48.2%; then, melt the weighed raw material of the samarium cobalt permanent magnet alloy in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3.9 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1207°C for 1h; then, cooling the sintered green body to 1175°C with the furnace for solid solution treatment, and the heat preservation time is 5h. After the solid solution treatment, the green body is quickly cooled to room temperature by air to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 5mm thick green body of samarium cobalt magnet slice by a slicer; S5. First, prepare a PrCu suspension solution. The preparation method of the PrCu suspension solution is the same as that of Example 1. Then, the PrCu suspension solution is evenly coated on the surface of the samarium cobalt magnet sheet and blown dry. Finally, the coated samarium cobalt magnet sheet is subjected to a diffusion treatment in a tube furnace. The diffusion treatment temperature is 1150° C. and the diffusion treatment time is 4 hours. The sheet is cooled and taken out of the furnace to obtain a samarium cobalt magnet diffusion sheet. The obtained samarium cobalt magnet diffusion sheet has a network Cu element segregation structure. S6. First, prepare a SnFe suspension solution. The method for preparing the SnFe suspension solution is the same as that in Example 1. Then, the SnFe suspension solution is evenly coated on the surface of the thin slice prepared in step S5 and blown dry. Finally, the coated samarium cobalt magnet thin slice is subjected to secondary diffusion treatment in a tube furnace. The secondary diffusion treatment temperature is 850° C., the diffusion treatment time is 4 h, and the thin slice is cooled and taken out of the furnace to obtain a samarium cobalt magnet secondary diffusion thin slice. S7. Perform aging treatment on the samarium cobalt magnet secondary diffusion sheet obtained after the treatment in step S6. The aging treatment process is as follows: heat the samarium cobalt magnet secondary diffusion sheet to 830°C, keep it warm for 4 hours, then cool it to 400°C at a rate of 1.5°C / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain Fe-rich high coercive force samarium cobalt magnet.

[0039] The magnetic properties of the Fe-rich high coercivity samarium cobalt magnet prepared in Example 5 are as follows: r =11.36kGs, magnetic energy product (BH) m =30.71MGOe, intrinsic coercivity H cj =35.25kOe. Comparative Example 5

[0040] Comparative Example 5 does not use the S5 primary diffusion and S6 secondary diffusion processes in Example 5, and the other preparation processes are the same as those in Example 5.

[0041] A method for preparing a sintered samarium cobalt permanent magnet comprises the following steps: S1. First, weigh a raw material of a samarium cobalt permanent magnet alloy according to the following composition and its weight percentage: Sm: 22.5%, Gd: 2%, Fe: 19%, Zr: 2.8%, Cu: 5.5%, Co: 48.2%; then, melt the weighed raw material of the samarium cobalt permanent magnet alloy in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3.9 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at 1207°C for 1h; then, cooling the sintered green body to 1175°C with the furnace for solid solution treatment, and the heat preservation time is 5h. After the solid solution treatment, the green body is quickly cooled to room temperature by air to obtain a solid solution state green body of samarium cobalt magnet; finally, the green body of samarium cobalt magnet is processed into a 5mm thick green body of samarium cobalt magnet slice by a slicer; S5. Perform aging treatment on the samarium cobalt magnet slice obtained after the treatment in step S4. The aging treatment process is as follows: heat the samarium cobalt magnet slice to 830° C., keep it at this temperature for 4 hours, then cool it to 400° C. at a rate of 1.5° C. / min, keep it at this temperature for 1 hour, and then quickly air-cool it to room temperature to obtain a sintered samarium cobalt permanent magnet.

[0042] The magnetic properties of the sintered samarium cobalt permanent magnet prepared in this embodiment 5 are: remanence B r =11.22kGs, magnetic energy product (BH) m =29.95MGOe, intrinsic coercivity H cj =35.12kOe.

[0043] It can be seen that the present invention can prepare sintered samarium cobalt products in production through secondary diffusion technology to meet various commercial application needs, and has a short process flow, low energy consumption, good economic benefits and broad application prospects.

[0044] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A diffusion preparation method for Fe-rich high coercivity samarium cobalt magnet, characterized in that: The following steps are involved: S1. First, weigh the samarium cobalt permanent magnet alloy raw material according to the following composition and its weight percentage: (Sm 1-x Re x ): 23%~25.5%, Fe: 16%~23%, Zr: 2.1%~3%, Cu: 4%~6%, and the balance is Co; wherein 0≤x≤0.3, Re is one or more of Pr, Nd, Gd, Dy, Tb, Er, Y or Ho; then, the weighed samarium cobalt permanent magnet alloy raw material is melted in a vacuum medium frequency induction melting furnace to obtain an alloy ingot with a thickness of 10 mm; S2, mechanically crushing the alloy ingot prepared in step S1 into alloy particles with a particle size of 0.5-2.5 mm; then, using a jet milling method to prepare the alloy particles into alloy powder with an average particle size of 3-5 μm; S3, weighing the alloy powder prepared in step S2 in an air atmosphere, then orienting and molding it in a 2T magnetic field, and finally cold isostatic pressing and molding it at a pressure of 200MPa to obtain a green body; S4, first, sintering the green body obtained in step S3 at a temperature of 1200-1215°C for 1-2h; then, cooling the sintered green body to 1160-1180°C with the furnace for solid solution treatment, and the heat preservation time is 4-10h, and then rapidly cooling to room temperature after solid solution treatment to obtain a solid solution state green body of samarium cobalt magnet; finally, processing the solid solution state green body of samarium cobalt magnet into a green body of samarium cobalt magnet slice by a slicer; S5. First, prepare a PrCu suspension solution; then, evenly coat the PrCu suspension solution on the surface of the samarium cobalt magnet sheet and blow dry; finally, perform a diffusion treatment on the coated samarium cobalt magnet sheet in a tube furnace, the diffusion treatment temperature is 1140-1150° C., the diffusion treatment time is 4-8 hours, and the sheet is cooled and taken out of the furnace to obtain a samarium cobalt magnet diffusion sheet; S6, first, prepare a SnFe suspension solution; then, evenly coat the SnFe suspension solution on the surface of the slice prepared in step S5 and blow dry; finally, subject the coated samarium cobalt magnet slice to a secondary diffusion treatment in a tube furnace, the secondary diffusion treatment temperature is 850-900°C, the diffusion treatment time is 2-4h, and the slice is cooled and taken out of the furnace to obtain a samarium cobalt magnet secondary diffusion slice; S7. Perform aging treatment on the samarium cobalt magnet secondary diffusion sheet obtained after the treatment in step S6. The aging treatment process is as follows: heat the samarium cobalt magnet secondary diffusion sheet to 800-850°C, keep it warm for 1-4 hours, then cool it to 400°C at a rate of 1.5°C / min, keep it warm for 1 hour, and then quickly cool it to room temperature with air to obtain Fe-rich high coercive force samarium cobalt magnet.

2. The diffusion preparation method of a Fe-rich high coercivity samarium cobalt magnet according to claim 1, characterized in that: In step S4, the thickness of the samarium cobalt magnet sheet is 3-7 mm.

3. The diffusion preparation method of a Fe-rich high coercivity samarium cobalt magnet according to claim 1, characterized in that: In step S5, the preparation method of the PrCu suspension solution is: first, 40% by mass of Pr and 60% by mass of Cu are smelted in an arc induction melting furnace to obtain a PrCu alloy ingot; then, the PrCu alloy ingot is crushed into a PrCu alloy powder with a particle size of 500-1000 nm by high-energy ball milling; finally, the PrCu alloy powder is mixed and stirred with anhydrous ethanol to obtain a PrCu suspension solution.

4. The diffusion preparation method of a Fe-rich high coercivity samarium cobalt magnet according to claim 1 or 3, characterized in that: In the step S5, the prepared samarium cobalt magnet diffusion sheet has a network-like Cu element segregation structure.

5. The diffusion preparation method of a Fe-rich high coercivity samarium cobalt magnet according to claim 1, characterized in that: In step S6, the SnFe suspension solution is prepared by: first, 5% by mass of Sn and 95% by mass of Fe are smelted in an arc induction melting furnace to obtain a SnFe alloy ingot; then, the SnFe alloy ingot is crushed into a SnFe alloy powder of 500-1000nm by high-energy ball milling; finally, the SnFe alloy powder is mixed and stirred evenly with anhydrous ethanol to obtain a SnFe suspension solution.

6. The diffusion preparation method of a Fe-rich high coercivity samarium cobalt magnet according to claim 3 or 5, characterized in that: The PrCu alloy powder and the SnFe alloy powder were mixed with anhydrous ethanol in a mass ratio of 1:9.

Citation Information

Patent Citations

  • Method for improving magnetic performance of samarium-cobalt permanent magnet material

    CN112038083A

  • 2-17 type samarium-cobalt permanent magnet material, and preparation method and application thereof

    CN113593882A

  • Permanent magnet and method for producing permanent magnet

    CN101563738A

  • Preparation method of R-T-B permanent magnet

    CN105469973A

  • Preparation method of high-remanence sintered Sm2Co17 permanent magnet

    CN116344192A

Cited By

  • High intrinsic coercive force 2 / 17 type iron-samarium-cobalt-rich permanent magnet material and preparation method thereof

    CN120356750A

  • A high intrinsic coercivity 2:17 type iron-rich samarium-cobalt permanent magnet material and its preparation method

    CN120356750B

  • Samarium-cobalt permanent magnet material and preparation method and application thereof

    CN120452971A

  • Large-orientation-size samarium-cobalt magnet and preparation method thereof

    CN121394089A